2023
DOI: 10.33545/surgery.2023.v7.i1a.972
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antifibrinolytic drug use in decreasing hemoglobin drop following Percutaneous Nephrolithotomy in Al-Hillah Province

Abstract: Introduction: Objective: To assess the effectiveness and safety of tranexamic acid in lowering postoperative haemoglobin and hematocrit decline, operational time, postoperative complications, and hospitalisation in percutaneous nephrolithotomy patients. Methods: A 40-patient Al-Hilla Teaching Hospital randomised controlled clinical trial ran from January 2020 through July 2022. All ultrasound-guided PCNL patients with renal stones were randomised into two groups. Group A consisted of 20 patients (13 males and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…One of the included studies, conducted by Al-Najjar et al, investigated the effects of TXA on patients who underwent percutaneous nephrolithotomy. [27] The study found that patients treated with TXA had shorter operative times and fewer requirements of blood transfusion.…”
Section: Updated Searchmentioning
confidence: 92%
“…One of the included studies, conducted by Al-Najjar et al, investigated the effects of TXA on patients who underwent percutaneous nephrolithotomy. [27] The study found that patients treated with TXA had shorter operative times and fewer requirements of blood transfusion.…”
Section: Updated Searchmentioning
confidence: 92%